Effects of Live Attenuated Vaccine and Wild Type Strains of Edwardsiella ictaluri on Phagocytosis, Bacterial Killing, and Survival of Catfish B Cells - Kordon, Adef O.; Kalindamar, Safak; Majors, Kara; Abdelhamed, Hossam; Tan, Wei; Karsi, Attila; Pinchuk, Lesya M. (Frontiers in Immunology, 2019)
Edwardsiella ictaluri,a Gram-negative facultative intracellular pathogen, is the causative agent of enteric septicemia of channel catfish (ESC). The innate functions of B cells have been demonstrated in several teleost fish, including zebrafish, rainbow trout, and channel catfish. Recently, our group has developed several protective E. ictaluri live attenuated vaccines (LAVs). However, the innate role of catfish B cells to phagocytose and destroy E. ictaluri wild-type (WT) and live attenuated vaccine (LAV) strains has not been evaluated. In this study, we assessed the efficacy of E. ictaluri WT and two LAVs on phagocytosis, microbial killing, and survival of catfish anterior kidney (AK) B cells. Initially, we documented active uptake of E. ictaluri WT and two LAVs in B cells by flow cytometry and light microscopy. Then, we observed the E. ictaluri strains-induced phagosome and/or phagolysosome formation in the cytoplasm of catfish magnetically sorted IgM+ B cells. Furthermore, we demonstrated that AK B cells were able to destroy the internalized E. ictaluri WT and LAV strains efficiently. Finally, we documented early and late apoptotic/necrotic manifestations induced by E. ictaluri in catfish AK B cells. In conclusion, our results suggest that both LAVs and WT strain exploite similar innate immunological mechanisms such as active phagocytic uptake, induced bactericidal activity as well as promote early and late apoptotic changes in catfish B cells. Our data suggest that phagocytic and microbicidal B cells can serve as professional APCs in initiation of protective adaptive immune responses against ESC in channel catfish.